Digitalization of Cultural Heritage as a Didactic Methodology: The case of Residencia de Estudiantes - Conde Melguizo, Rafael; Blanco Marcos, Jessica (Street Art & Urban Creativity, 2025)
The New Urban Agenda published by UN-Habitat sets the goal of protecting and safeguarding the world’s cultural and natural heritage, especially local and regional heritage that is at risk of being marginalized in the face of global acculturation trends. Aware of the increase in the number of heritage consults on digital platforms and the conservation opportunity that this format implies, UNESCO drafted in 2015 the United Nations Recommendation on the Preservation of and Access to Documentary Heritage included in digital form. This article proposes taking advantage of this process for the educational use of digitized heritage. The design of educational activities included in the editorial heritage digitized by the Residencia de Estudiantes by the PLATA project of UDIT university is proposed as a standard, incorporating artificial intelligence tools and cloud services that allow for a deeper understanding of its educational use by exploiting the possibilities that digitalization allows.